Kepercayaan Monoteisme di dalam Agama Hindu - Muhamat @ Kawangit, Razaleigh (Jurnal Usuluddin, 2003)
This article reviews the doctrine of monotheism in Hindu Religion. It discusses the strength of the bases of monotheism, internal and external factors of Hindu monotheism doctrine and the practical theory of monotheism as stated in the holy book of Veda. The scope of this article is further broaden to include the aspects of worship, culture and superstition and social lives of the worshippers especially in view of practices of monotheism. Finally it is concluded that the doctrine of Hindu monotheism is greatly influenced by the aspect of politheism, directly and indirectly. Practically, Hindu monotheism theory has been adapted with respect to substances of polytheism especially in the worships.